The governance of temporal goods of private associations: from Code regulation to estatutory realization - Pérez Sanjuán, Raquel (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2016)
The autonomy enjoyed by private associations of the faithful concerning their direction is also reflected on the governance of the goods, since can. 1257 §2 establishes that «the temporal goods of a private juridic person are governed by its own statutes but not by these canons unless other provision is expressly made». This statement opens up controversial issues, such as the limits of bona ecclesiastica described in can. 1257 §1, governance over the goods of private juridic persons, or the CIC 1983 norms which expresse affect these associations. Coming to know how the statutes of seven private international associations describe the administration of goods, allowed underscoring some general critical reflections which help to complete the overview offered by the code regulation.
Keywords: Bona ecclesiastica; International Associations; Statutes